Report of the 3rd Joint Australia-Japan Workshop 'Australia and Japan collaboration in Antarctic Science' - So Kawaguchi; Watanabe, K (2016)
The 3rd Joint Workshop on Australian and Japanese Collaboration in Antarctic Science was held at the Institute for Marine and Antarctic Studies, University of Tasmania, Hobart, Australia on the 6th and 7th of August 2015. The primary aim of the workshop was to identify and highlight current collaborations and campaigns, and those planned for the next few years, and to share this information to maximize the synergy and opportunities for East Antarctic science within the international context. Discussion covered a range of issues including research areas of common interest, resource sharing, development of joint research proposals, multinational research coordination, and future meetings.